A cross-sectional assessment of knowledge, attitudes and self-perceived effectiveness of complementary and alternative medicine among pharmacy and non-pharmacy university students - Mariam Ashraf; Hamid Saeed; Zikria Saleem; Hassaan Anwer Rathore; Fawad Rasool; Eman Tahir; Tooba Bhatti; Javeria Khalid; Iqra Bhatti; Ayesha Tariq (BMC, 2019)
Abstract Background Traditional medicine has always been Pakistan's cultural heritage, providing health care to a large part of its population. Thus, we aimed to assess and compare the knowledge, attitude, and perception about complementary and alternative medicine (CAM) between pharmacy and non-pharmacy students, the results of which may be helpful in devising national health-education policy. Methods A cross-sectional study was conducted by enrolling 937 students, pharmacy (437) and non-pharmacy (500), of Punjab University, Lahore. A self-administered questionnaire was used for data collection. Data were analyzed using SPSS. (IBM v22). Results Data suggested that majority of students knew about the use of traditional herbs and considered massage (P: 84.4%, NP: 82%, p = 0.099), homeopathy, herbs (P: 86.5%, NP: 81%, p = 0.064], yoga [P: 357 (81.7%), NP: 84%), p = 0.42] and spiritual healing (P: 85.6%, NP: 86.2%, p = 0.55) as effective and least harmful CAM modalities. The pharmacy students had better knowledge about CAM modalities compared to non-pharmacy students. Despite utilizing non-reliable sources of CAM information and their belief that CAM is practiced by quacks, the majority of students had positive attitudes and perceptions about CAM usage. Students also believed that CAM had a positive impact on health outcomes [P: 3.19 ± 1.04, NP: 3.02 ± 1.09, p = 0.008] and acceded to include CAM in the pharmacy curriculum. However, non-pharmacy students scored higher in their beliefs that CAM usage should be discouraged due to the non-scientific basis of CAM (P: 3.04 ± 0.97, NP: 3.17 ± 1.02, p = 0.028) and a possible threat to public health (P: 3.81 ± 1.74, NP: 4.06 ± 1.56, p = 0.02). On the other hand, pharmacy students believed that patients might get benefits from CAM modalities (P: 4.31 ± 1.48, NP: 4.12 ± 1.45, p = 0.02). Majority of students perceived that spiritual healing is the most useful and safer CAM modality, while acupuncture (P: 25.4%, NP: 21.8%, p = 0.0005), hypnosis (P: 26.8%, NP: 19.6%, p = 0.001) and chiropractic (P: 18.8%, NP: 11.6%, p = 0.0005) were among the harmful ones. Conclusion In conclusion, despite poor knowledge about CAM, students demonstrated positive attitudes and beliefs regarding CAM. They exhibited better awareness about yoga, spiritual healing/prayer, herbs, and massage. Students also showed willingness to advance their knowledge about CAM and favored its inclusion in the curriculum.